Why and How Identity Should Influence Utility - Philipp C. Wichardt (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2007)
This paper provides an argument for the advantage of a preference for identity-consistent behaviour from an evolutionary point of view. Within a stylised model of social interaction, we show that the development of cooperative social norms is greatly facilitated if the agents of the society possess a preference for identity consistent behaviour. As cooperative norms have a positive impact on aggregate outcomes, we conclude that such preferences are evolutionarily advantageous. Furthermore, we discuss how such a preference can be integrated in the modelling of utility in order to account for the distinctive cooperative trait in human behaviour and show how this squares with the evidence.
urn:nbn:de:bvb:19-epub-13359-7
Keywords: A13; C70; C90; D01; Z13; 330; cognitive dissonance; fairness; identity; reciprocity; social Norms; social preferences; utility